NASOPHARYNGEAL CARCINOMA CHARACTERISTIC AT ARIFIN ACHMAD HOSPITAL IN JANUARY-OCTOBER 2018 - Harianto (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Introduction: Nasopharyngeal carcinoma is the most head and neck malignancy worldwide that is capable of performing distant metastasis and potentially to relapse. Indonesia prevalence of cancer estimate 1.4% or approximately 347.792 population and the highest found in D.I Yogyakarta, whereas Riau province counted 0.7% or around 4.301 population. This concludes the nasopharyngeal carcinoma stand as the 4th of the most malignancy in Indonesia after the mamae carcinoma, cervix carcinoma, and skin tumor. Objective: The purpose of this study is to asses the characteristic of NPC patient in Arifin Achmad Hospital Riau Province involving the incidence, gender, age, histopathology classification, distribution by the period and the therapy. Material and method: Retrospective cross-sectional approach with the descriptive presentation to assess the entire population of nasopharyngeal carcinoma based on gender, age, histopathology classification and treatment in January to October 2018. The data obtained from several data provide unit and process into a frequent and distribution table. Result: The number of the cases obtained include the new case and old case was 137 cases sequently 62 new cases and 75 old cases. Men were most affected and the commonest occurring in range 40-60 years. All the most histopathology classification was the undifferentiated nasopharyngeal carcinoma. Most of the patient treated with chemotherapy. Conclusion: NPC was the highest incidence of the head and neck malignancy commonly in men. All the most occurred in early elderly and the highest histopathology type was undifferentiated nasopharyngeal carcinoma (WHO Type III). Chemotherapy was the choice to treat the patient.